Making intense skills training work at scale: Evidence on business and labor market outcomes in Tanzania - Margherita Calderone; Nathan Fiala; Lemayon Lemilia Melyoki; Annekathrin Schoofs; Rachel Steinacher (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Improving youth labor market outcomes is a primary concern for countries around the world. We conduct a randomized controlled trial in Tanzania on an intense gender-sensitive skills training program that worked with over 53,000 youth in the region. After two years, we find the program increased women's economic outcomes, including income, savings, as well as engagement in the labor market, and quality of jobs for all participants. We find no significant effects on economic outcomes for male participants. We also find significant effects on hard skills for both women and men and soft skills for women in terms of self-awareness and confidence. In a cross experiment with micro-grants, we find smaller but economically significant effects on all outcomes for both genders. From a monetary perspective the training program is very cost-effective, paying for itself within 32 months when targeting both women and men.
Keywords: J24; J68; L26; M53; O12; C93; 330; Business training; soft skills; youth unemployment; microenterprises; Tanzania